Enhancing learning activity and learning outcomes in the electrical installation course using augmented reality - Bakri, Hasrul; Mukhlisin, Mukhlisin; Sukma, Indra; Dzar Faraby, Muhira (Jurnal Inovasi Teknologi Pendidikan, 2025)
Student engagement and learning outcomes are two interrelated aspects that determine the effectiveness of the teaching and learning process. This study aimed to analyse the impact of Augmented Reality (AR)-based learning on student engagement and academic achievement compared to conventional instruction. The research employed a quasi-experimental design with an experimental and a control class. Student engagement was assessed through cognitive, affective, and psychomotor dimensions, while learning outcomes were measured using a post-test. The findings revealed that AR-based learning significantly improved student engagement across all domains, with average scores of 91.35% in the cognitive domain, 87.54% in the affective domain, and 90.04% in the psychomotor domain, all surpassing the success threshold of >75%. Conversely, the control class achieved only 79.67% in the cognitive domain, while the affective (66.62%) and psychomotor (69.34%) domains fell short of the expected standard. Similarly, the experimental group demonstrated higher academic performance, with a mean post-test score of 91.21, compared to 66.46 in the control group. These results indicate that AR-based learning not only fosters active student participation but also enhances academic achievement. The study implies that integrating innovative, technology-enhanced strategies in higher education is essential for promoting holistic learning that prepares graduates for professional and digital-era challenges.